Eksekusi Putusan Perdata Pasca Mediasi Elektronik Gagal: Penyebab dan Solusi Normatif menurut PERMA No. 3 Tahun 2022 - Muhammad Dhimas Khoirul Alam; Ruben Theofilus Chrysostomus; Anggi Sri Haryati Simarmata (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2026)
The development of information technology has transformed civil dispute resolution mechanisms in Indonesia, most notably through the issuance of Supreme Court Regulation (PERMA) Number 3 of 2022 on Electronic Mediation in Courts. Despite the normative framework it provides, the implementation of electronic mediation continues to face persistent challenges, particularly regarding limited digital infrastructure, low digital literacy among disputing parties, and insufficient technical capacity of mediators. More critically, when electronic mediation fails to produce a settlement agreement, the subsequent enforcement of civil court decisions encounters serious normative gaps not yet adequately addressed by existing legal instruments. This study aims to identify and analyze the causes of civil judgment enforcement failures arising in the context of failed electronic mediation under PERMA Number 3 of 2022, and to propose normative solutions for the identified regulatory gaps. Using a normative juridical method supported by statutory, conceptual, and case approaches, this study finds that the primary causes of enforcement failure include the absence of clear legal standards governing electronically signed peace deeds, weak synchronization between PERMA Number 3 of 2022 and civil procedural law on execution, and procedural obstacles in enforcing decisions that originate from electronic proceedings. This study recommends targeted regulatory reform to ensure that peace agreements resulting from electronic mediation carry unambiguous executorial force and that enforcement mechanisms are adapted to accommodate the distinctive characteristics of electronic dispute resolution.